Respon Pertumbuhan Planlet Anggrek Phalaenopsis Hibrida Terhadap Pemberian Dua Jenis Pupuk Daun Dan Benziladenin Selama Aklimatisasi - Zasari, Maera; Yusnita, .; Susriana, . (Universitas Bangka Belitung, 2014)
Optimization of planlets growth during acclimatization can be done by using plant growth regulator. This research was aimed to know the effect of two foliar fertilizer and benzyladenin on the growth of Phalaenopsis hybrid orchid planlets during acclimatization stage. The treatment was Growmore and Bayfolan as the foliar fertilizer with the various concentrate of benzyladenin (BA) at BA 0 mg/l, BA 15 mg/l and BA 30 mg/l. The results showed that Growmore foliar fertilizer had the better response of plant height and fresh weight plant compared to Bayfolan foliar fertilizer. BA 30 mg/l was increased the leaf number, and BA 15 mg/l and 30 mg/l was decreased root length and fresh weight plant. There was no interaction between foliar fertilizer and benzyladenin on the growth of Phalaenopsis hybrid orchid planlets.